Kajian Arsitektur Biophilic Pada Bangunan Resort sebagai Peningkatan Lingkungan “Healing” - Gilang Ardyansyah; Syaifuddin Zuhri (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2025)
Abstract: This study examines the application of biophilic architecture principles in resort buildings to enhance a